Effect of annealing on magnetic properties of iron-based soft magnetic composites with iron oxide insulator - Choi, K. D.; Lee, S. Y.; Kim, H. Y.; Hwang, J. S.; Huh, J. Y.; Yi, K. W.; Byun, Ji Young (Elsevier BV, 2022)
This study introduces a closed oxidation system for forming an oxide insulating film on the surface of pure-iron powder, using an oxygen concentration analyzer to monitor the progress of the reaction. The closed system is designed such that all the supplied oxygen completely reacts to form an oxide film at 500 degrees C. It is established that the oxide-film thickness can be controlled by the quantity of oxygen supplied. XRD analysis indicates that the oxide film is mostly composed of the Fe3O4 phase. The TEM oxygen mapping image shows that the oxide film is uniformly and completely formed on the surface of pure-iron powder. Further, toroidal cores are fabricated by compacting the pure-iron powder coated with an oxide insulating film. To relieve the strain generated during compaction, annealing is performed in the 400-700 degrees C range. At annealing temperatures below 550 degrees C, the change in the core loss is not considerable (85.0 W/kg at room temperature (23 degrees C) and 94.8 W/kg at 550 degrees C). However, above 550 degrees C, sudden increase in the core loss is observed (505.9 W/kg at 700 degrees C). The Fe3O4 in the oxide film reacts with the Fe phase to form FeO above 570 degrees C, which is the eutectoid temperature. This phase transformation damages the insulation of the oxide film, resulting in a sharp increase in the eddy current loss. The hysteresis loss decreases from 71.2 W/kg to 43.9 W/kg with the increase in the annealing temperature. It is determined that the pure-iron powder core coated with an oxide insulating film is heat-resistant up to a temperature of 550 degrees C.